The diversity of the circumgalactic medium around z = 0 Milky Way-mass galaxies from the Auriga simulations. Issue 1 (21st June 2019) - Hani, Maan H; Ellison, Sara L; Sparre, Martin; Grand, Robert J J; Pakmor, Rüediger; Gomez, Facundo A; Springel, Volker
ABSTRACT: Galaxies are surrounded by massive gas reservoirs (i.e. the circumgalactic medium; CGM) which play a key role in their evolution. The properties of the CGM, which are dependent on a variety of internal and environmental factors, are often inferred from absorption line surveys which rely on a limited number of single lines-of-sight. In this work we present an analysis of 28 galaxy haloes selected from the Auriga project, a cosmological magneto-hydrodynamical zoom-in simulation suite of isolated Milky Way-mass galaxies, to understand the impact of CGM diversity on observational studies. Although the Auriga haloes are selected to populate a narrow range in halo mass, our work demonstrates that the CGM of L ⋆ galaxies is extremely diverse: column densities of commonly observed species span ∼3 − 4 dex and their covering fractions range from 5 to 90 per cent . Despite this diversity, we identify the following correlations: 1) the covering fractions (CF) of hydrogen and metals of the Auriga haloes positively correlate with stellar mass, 2) the CF of H i, C iv, and Si ii anticorrelate with active galactic nucleus luminosity due to ionization effects, and 3) the CF of H i, C iv, and Si ii positively correlate with galaxy disc fraction due to outflows populating the CGM with cool and dense gas. The Auriga sample demonstrates striking diversity within the CGM of L ⋆ galaxies, which poses a challenge for observations reconstructing CGM characteristics from limited samples, and also indicates that long-term merger assembly history and recent star formation are not the dominant sculptors of the CGM.